Complete Response to Sorafenib Rechallenge in a Patient with Metastatic Renal Cell Carcinoma - Ryo Kasahara; Noboru Nakaigawa; Kazuki Kobayashi (Case Reports in Oncological Medicine)
A 79-year-old Japanese man underwent a medical examination for hoarseness. Computed tomography revealed a left renal tumor, and radical nephrectomy was performed. The tumor was a clear cell carcinoma. Fourteen months after the operation, the tumor had metastasized to the spleen, right lung, and retroperitoneal lymph nodes. We initiated molecular targeted therapy sequentially with sorafenib, sunitinib, and axitinib and then conducted a rechallenge with sorafenib. His metastatic lesions had completely vanished 5 months after initiation of the rechallenge. Ten months after the rechallenge, lumbar vertebral body metastasis appeared. However, we consider that the sorafenib rechallenge was effective because of the very slow growth of the metastatic lesion, with no other metastasis for 30 months, at the time of writing this report. Approximately 7 years after the first local recurrence, he remained alive, with relatively normal daily functioning.